The choice to run - Tan, Chen Jim (2014)
The Singapore state government’s paternalistic style of governance has allowed it to legitimately and effectively manage the welfare of the nation and its citizens. The citizen’s health is of social and economic concern of the state which it tackles through the increase of the budget towards the healthcare infrastructure and encourages its citizens to adopt a healthy lifestyle. Through its repertoire of strategies to persuade Singaporeans to adopt the desired lifestyle though sports participation, ‘running’ achieved the best results. This paper will discuss how running in Singapore has been developed as a means for social control to promote the ideals of health and meritocracy; and gauge its effectiveness while highlighting the possible consequence it has on the citizens participating in the sport, framed using conceptualizations of Foucault’s “Technologies of the Self”: Ethical Self-care, Critical awareness and Aesthetic stylization.